¿Qué significa para un yo ser puesto? Análisis de los capítulos 1 y 2 de la Primera Parte de La enfermedad mortal de Kierkegaard - Rodríguez, Pablo Uriel (2025)
“What is a human being?” and “What is the self?” With this questions, Anti-Climacus–the famous pseudonym of Kierkegaad– begins The Sickness unto Death (1849). The answer follows promptly. A human self is a relationship that relates to itself. This self-relationship has been posited by an other (Andet) or a power (Magt). By relating to itself, this self-relationship thereby relates to this other or power. This paper aims to clarify what it means for the self to be a derived self-relation. To achieve this goal, it analyzes the first two chapters of Anti-Climacus’ book. This analysis is grounded in Kiekegaard’s reflections on the interplay between human freedom and divine omnipotence.